Is Classroom Cheating Related to Business Students' Propensity to Cheat in the "Real World"? - Lawson, Raef A. (Journal of business ethics, 2004)
Previous studies have reportedstudents' widely held belief that they are moreethical than businessmen. On the other hand,widespread cheating among college students hasbeen reported. This paper examines thisinconsistency between the beliefs of collegestudent regarding the need for ethical behaviorin a business setting and their actions in anacademic setting., The results of this study indicate that whilestudents are generally upset with cheating intheir class, a large proportion of themnonetheless engage in such behavior. It wasfurther found that students have a goodunderstanding of what constitutes ethicalbehavior in the business world and the need forsuch behavior. However, they also believe thatbusiness people fail to act in an ethicalmanner, and that they may need to actunethically to advance their careers., Students' concern with business ethicscontrasted sharply with their own lack ofpersonal ethics. This "paradox" is consistentwith the idea that students view thepracticality of an action as being moreimportant than its ethicality. This belief isa cause for concern and indicates a need forstudents to sharpen their ethicaldecision-making skills in complex real-worldtype settings.